Indonesia's Position as a Maritime Axis in the Global Logistics Chain - Aritonang, Felicia Nathania Tondi; Arkady, Joanna Clementine; Torindatu, Lovely Andrea Rebecca; Silalahi, Verry Albert Jekson Mardame (Yayasan Inspirasi Merah Putih Indonesia, 2025)
Indonesia is strategically positioned as the world's largest archipelagic country with more than 17,000 islands and vital shipping lanes connecting the Indian and Pacific Oceans, making it a global maritime logistics hub. However, this potential is constrained by logistics infrastructure disparities, especially in the eastern region which faces limitations in port capacity and shipping frequency. This study aims to analyze Indonesia's maritime policy 2021-2025 in overcoming logistics challenges, improving inter-island connectivity, and integrating modern technology for operational efficiency. The results of the study show that the Sea Toll program has succeeded in reducing price disparities between islands through increased connectivity, although the efficiency of loading and unloading and warehousing still needs to be improved. Initiatives such as real-time tracking and satellite-based AIS systems have been proven to improve port security and productivity. The conclusions of the study emphasize the importance of policy harmonization, investment in strategic ports (such as Patimban), and the implementation of sustainable practices to maximize Indonesia's geographical advantage. Global collaboration through events such as Indonesia Maritime Week 2025 and the adoption of digitalization are key to strengthening Indonesia's position as a sustainable global maritime hub.